Realism, liberalism and the European debt crisis. - Chen, Priscilla Shiying. (2013)
The European debt crisis vindicated both the realists and liberals and is a synthesis of the dialectical interplay between realism and liberalism. Economic warfare is the major form of war being fought among countries, rather than acting as a supplement to military intervention. The unprecedented creation of a regional institution, the EU seems to have notched a major victory for the liberalist’s school, along with the increasing power of financial institutions such as the IMF. But, the cracks evident within the EU, along with the unfolding of the EU debt crisis have illustrated how key tenets of realism such as self-interest, states as the main key actors and anarchy continue to thrive. The European debt crisis is a double-edged sword. While dealing significant damage to the pillars of the liberal order of political economy, it also brings about numerous opportunities for change, which, if properly exploited can increase the prowess of the EU and might enhance regional stability and further institutionalize the region in the long-term. The European debt crisis will thus illustrate the creation of a new form of “realistic liberalism”.